2022
DOI: 10.26466/opusjsr.1064280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performances of MCDM Methods under Uncertainty: An Analysis on Bist SME Industry Index

Abstract: MCDM is a sort of ranking and selection methodology widely used both in daily life and in disciplines such as social, science, health, informatics, and engineering. However, the selection of an appropriate MCDM method is a common and chronic problem of these disciplines. Because the issue of determining the most appropriate method among MCDM methods has not been clarified yet. Since the algorithms of more than a hundred MCDM methods currently that are in use are different, the ranking they produce or the "best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…It has also been confirmed to be superior to TOPSIS when used in multi-criteria decision making in the selection of chemical manufacturing processes [31]. In research [32], when used to evaluate the financial performance of companies, FUCA was confirmed to be equivalent to the PROMETHEE method, and better than COPRAS, TOPSIS, SAW, CODAS, and MOORA. When used in another study on evaluating the financial performance of companies, FUCA was also found to be as effective as the PROMETHEE method, and better than the TOPSIS, GRA, S-, WSA, SAW, COPRAS, MOORA, and LINMAP [33].…”
Section: Introductionmentioning
confidence: 90%
“…It has also been confirmed to be superior to TOPSIS when used in multi-criteria decision making in the selection of chemical manufacturing processes [31]. In research [32], when used to evaluate the financial performance of companies, FUCA was confirmed to be equivalent to the PROMETHEE method, and better than COPRAS, TOPSIS, SAW, CODAS, and MOORA. When used in another study on evaluating the financial performance of companies, FUCA was also found to be as effective as the PROMETHEE method, and better than the TOPSIS, GRA, S-, WSA, SAW, COPRAS, MOORA, and LINMAP [33].…”
Section: Introductionmentioning
confidence: 90%
“…The comparative analysis evaluates the ranks that are obtained from various C-MCDM approaches using three similarity metrics, including SRC, WRC, and RSC [ [107] , [108] , [109] , [110] ]. This analysis is necessary to determine whether the two rankings are consistent or unreliable and to decide whether the order of the rankings is valid.…”
Section: Multi-criteria Decision-making Algorithmsmentioning
confidence: 99%
“…The FUCA (Faire Un Choix Adéquat) method has been identified as superior to the WSA (Weighted Sum Approach) method for finding optimal solutions for the financial use of companies [1]. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) me thod has been determined to outperform the MOORA (Multiobjective Optimization On the basis of Ratio…”
Section: Introductionmentioning
confidence: 99%